Breeding strategy for resistance to Striga asiatica (L.) Kuntze based on genetic diversity and population structure of tropical maize (Zea mays L.) lines - Gasura, Edmore; Nyandoro, Brian; Mabasa, Stanford; Setimela, Peter S.; Kyalo, Martina; Yao, Nasser (Springer, 2022)
Maize (Zea mays L.) is a major staple crop in southern Africa and is produced on millions of hectares. However, its yield is greatly reduced by Striga spp. a witchweed which is causing US$ 7 billion losses annually. Use of host resistance could be an effective way of controlling Striga spp. and resistance to Striga spp. is quantitative, mainly controlled by additive gene action. Understanding the population structure and genetic diversity is therefore key in designing an effective breeding program targeting grain yield heterosis and resistance to Striga spp. The aim of this study was to determine the genetic diversity and population structure of the key germplasm from tropical Africa. This information could guide in the identification of heterotic groups and potential testers required to kick start a maize breeding program for Striga asiatica (L.) Kuntze in southern Africa. A total of 222 maize inbred lines from IITA and CIMMYT were used in this study. The materials were genotyped using the genotyping-by-sequencing method. A total of 45, 000 SNP markers were revealed, and these were subjected to analysis of molecular variance, structure analysis and clustering using the Gower’s distance and neighbor joining algorithm. Molecular variance was lager within individuals (91%) than among populations (9%). The inbred lines clustered into three major groups, with the IITA germplasm clustering separately from CIMMYT germplasm. A breeding strategy for S. asiatica resistance was proposed with the aim of increasing genetic gains in both the resistance and grain yield.